Image Classification Based on Hybrid Compression System - Nidaa F. Hassan; Noor Emad A. lhamza (Engineering and Technology Journal, 2015)
Due to the fast development of internet technologies and multimedia archives are growing rapidly, especially digital image libraries which represent increasingly an important volume of information, it is judicious to develop powerful browsing computer systems to handle, index, classify and recognize images in database. In this paper anew algorithm image classification is proposed. Thispaper presents an efficient content-based image indexing technique for searching similar images using daubechies wavelet with discrete cosine transform. The aim of this work was to realize the image classification using hybrid compression system. The image was classified using 10 classes.